2018
DOI: 10.3390/jcm7120509
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ST-Elevation Acute Myocardial Infarction Prevalence by Gender Assessed Age Pyramid Analysis—The Piramyd Study

Abstract: Introduction: Recent studies reported a decrease in the incidence of acute myocardial infarction. This favorable evolution does not extend to young women. The interaction between gender, risk factors and myocardial infarction incidence remains controversial. Objective: To compare the evolution of the age pyramid of patients with ST-elevation myocardial infarction (STEMI) according to gender. Methods: Data from patients with STEMI managed in pre-hospital settings prospectively collected in the greater Paris are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…In numerous studies, the interaction between gender, risk factors and incidence of myocardial infarction remains controversial 13 . Some studies have suggested specific gender‐intrinsic‐causes even after adjustment for age and other risk factors, 2,8,14 while others have failed to establish an association between gender and mortality 15,16,17 …”
Section: Introductionmentioning
confidence: 99%
“…In numerous studies, the interaction between gender, risk factors and incidence of myocardial infarction remains controversial 13 . Some studies have suggested specific gender‐intrinsic‐causes even after adjustment for age and other risk factors, 2,8,14 while others have failed to establish an association between gender and mortality 15,16,17 …”
Section: Introductionmentioning
confidence: 99%
“…These results could denote that, in Mexico, the preventive measures are not enough to moderate the incidence of STEMI and that there are factors that could be conditioning to a more severe form of heart attack. This unfavourable evolution in our country is in line with the increase in the prevalence of cardiovascular risk factors such as hypertension, smoking, T2DM, and dyslipidaemia, among others, and this trend is contrary to the decrease in STEMI cases reported in countries such as the United States and Europe [ 10 ].…”
Section: Discussionmentioning
confidence: 88%
“…The same phenomenon has been suggested in women [ 31 ]. Women are becoming more numerous in the older age groups in accordance with the demographics of the populations in France and most Western countries [ 32 , 33 ]. The evolution of the prevalence of cardiovascular risk factors is consistent with the age groups [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%